2009
DOI: 10.1038/ajh.2009.98
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Atrial Fibrillation Using a Modified Microlife Blood Pressure Monitor

Abstract: This device is able to detect AF with high sensitivity and specificity. Use of this device by patients who monitor their blood pressure at home may help detect asymptomatic AF and allow for treatment prior to the development of a stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
104
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 13 publications
7
104
1
2
Order By: Relevance
“…In line with the findings of Wiesel et al, 10 and after testing several approaches including single, duplicate and triplicate measurements, and one of two, one of three and two of three positive measurements needed for diagnosis, these data confirmed that triplicate measurements, in which two of them were required to make an AF diagnosis, is the optimal approach in terms of diagnostic accuracy (Table 2). In fact this screening tool appears to be more accurate in diagnosing AF than the general practitioners' diagnosis carried out by ECG together with an interpretative software.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In line with the findings of Wiesel et al, 10 and after testing several approaches including single, duplicate and triplicate measurements, and one of two, one of three and two of three positive measurements needed for diagnosis, these data confirmed that triplicate measurements, in which two of them were required to make an AF diagnosis, is the optimal approach in terms of diagnostic accuracy (Table 2). In fact this screening tool appears to be more accurate in diagnosing AF than the general practitioners' diagnosis carried out by ECG together with an interpretative software.…”
Section: Discussionsupporting
confidence: 84%
“…9 A recent study by the same group tested the same device as in this study in 205 subjects, of whom 52 had AF on ECG. 10 The sensitivity and specificity of a single measurement for detecting AF was 98 and 88%, respectively. For three measurements, in which two of them were required to diagnose AF, the diagnostic accuracy was improved (sensitivity, 100%; specificity, 89%), 10 that is identical with the finding of this study ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The remaining time intervals were used to calculate the irregularity index. If the irregularity index exceeded a threshold value of 0.06, the rhythm was considered irregular 9. …”
mentioning
confidence: 99%
“…The stroke prevention guidelines recommend screening for AF by checking the pulse during blood pressure monitoring and obtaining electrocardiograms (ECG) in patients older than 65 years of age. A recent study showed the utility of a novel blood pressure monitor in detecting AF during routine checks [44].…”
Section: Impact Of Long-term Monitoring For Detecting Atrial Fibrillamentioning
confidence: 99%